Effect of Self Therapy - Helps Groups Against Family Coping With Mental Retardation Children In SLB - C Purbalingga - Ruti Wiyati; Welas Haryati; Dyah Wahyuningsih (Jurnal Riset Kesehatan, 2012)
The design of this study is a "Quasi experimental pre and post test with control group by the intervention of self-help groups. The intervention group the day I: pre-test, the third day of self-helppgroups six sessions over three weeks and the fourth week post-test. In the control group pre-test day l and day seven post test. Way of purposive sampling to sample as many as 40 families. Means of collecting data using questionnaires family characteristics and family coping questionnaire. The results showed an increase in the ability of families with mentally retarded children were significantly (p value = 0.000). Recommended to establish and implement self-helppgroups for families who have children mental retardation.